Enhancing microbial-induced calcium carbonate precipitation efficiency in calcareous sands through ferric ion additives: A comprehensive experimental investigation - Jin Zhu; Renjie Wei; Di Dai; Liangliang Li; Zhiyang Shang; Zhao Jiang; Jie Peng (PLoS ONE, 2025)
In recent years, the reinforcement of calcareous sands using the microbially induced calcium carbonate precipitation (MICP) method has emerged as a prominent research area. Nevertheless, a significant drawback of the MICP method is that multiple treatments with the cementing solution are required to achieve the desired improvement effect. To address this limitation, this study proposes an optimized MICP strategy through adding the ferric ion into cementing solutions. The effectiveness of the proposed method was investigated by analyzing the precipitation of CaCO3, unconfined compressive strength (UCS) and permeability coefficient through aqueous solution test and sand column reinforcement test. Experimental results revealed that ferric ion incorporation significantly altered CaCO3 crystal morphology and particle size distribution in aqueous solution test. In sand column tests, specimens treated with cementing solution with ferric ion achieved the UCS of 2.83 MPa after five injection cycles, representing a 15-fold increase compared to conventional MICP-treated specimens under the same test conditions. At the same time, permeability coefficients decreased by two orders of magnitude relative to untreated sand. The micro-structure analysis showed that ferric ions were involved in the reaction to generate a clogging precipitate, which changed the distribution of bio-CaCO3 in the pores of the soil, thereby improving the cementation efficiency. These findings indicate that the addition of ferric ion can overcome the shortcoming of frequent treatment of cementing solution in MICP-reinforced calcareous sand, and provide new insights for the development of effective biological grouting strategies.